The Effect of Using Digital Comic Strips in Reading on Young Learners - Ni Putu Ayu Puspa Yuliandari (International Journal of Digital Learning on Languages and Arts, 2025)
The purpose of this study is to investigate the effect of using digital comic strips in teaching English reading text at SDN 3 Banjar Jawa by using Comic & Meme Creator. A quasi-experimental by pre-test and post-test non-equivalent control group was applied as a design for the study. The sample of the study was two classes in third grade (III A and III B) that consisted 30 students for each class. The data were processed by using SPSS 24.0 to analyze paired sample t-test. The finding of the study shown the significant effect on students’ English reading score by using digital comic strips. The data of paired sample t-test shown the mean of post-test on treatment class was 84 and control class was 77. The hypothesis testing of treatment class showed -10.698 and the score of sig. (2-tailed) is 0.000. According to the null hypothesis (Ho) which the score is 0.05, the score of sig. (2-tailed) of the data was smaller than the Ho. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (H⍺) was accepted. In conclusion, there is a significant effect of using digital comic strips in teaching English reading text at SDN 3 Banjar Jawa.